Perceptions, barriers and enablers on salt reduction in the out-of-home sectors in Malaysia (MySaltOH) from the perspective of street food vendors, caterers and consumers - Zainorain Natasha, Zainal Arifen; Hasnah, Haron; Suzana, Shahar; Zaliha, Harun; Michael, Viola; You, Yee Xing; Zahara Abdul, Manaf; Hazreen Abdul, Majid; Chia, Yook Chin *; He, Feng J; Brown, Mhairi Karen; MacGregor, Graham A (Cambridge University Press, 2023)
Objective: To explore the perspectives, barriers and enablers on salt reduction in out-of-home sectors in Malaysia among street food vendors, caterers and consumers.